2020
DOI: 10.1002/ptr.6845
|View full text |Cite
|
Sign up to set email alerts
|

Biochanin A induces a brown‐fat phenotype via improvement of mitochondrial biogenesis and activation ofAMPKsignaling in murineC3H10T1/2 mesenchymal stem cells

Abstract: In this study, we investigated the effect of Biochanin A (BioA), an O‐methylated isoflavone on the brown‐fat phenotype formation and on the associated thermogenic program including mitochondrial biogenesis and lipolysis in C3H10T1/2 MSCs. Our data demonstrates that Treatment with BioA in an adipogenic differentiation cocktail induced formation of brown‐fat–like adipocytes from C3H10T1/2 MSCs without treatment with a known browning inducer (rosiglitazone or T3) at an early stage of differentiation. The formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…The fact that Angptl4 expression is induced by anti-diabetic drugs further fuels the controversy about the role of ANGPTL4 in metabolic homeostasis as discussed earlier. Finally, Lect2 expression was not found to be significantly sensitive to anti-diabetic drugs and phytoestrogens, while Fgf21 expression was strongly stimulated by rosiglitazone and genistein in MPH, in agreement with previous studies in hepatocytes or mesenchymal stem cells [ 125 , 126 ]. However, we could not confirm the induction of Fgf21 expression by metformin as previously suggested by other studies [ 127 , 128 ].…”
Section: Discussionsupporting
confidence: 90%
“…The fact that Angptl4 expression is induced by anti-diabetic drugs further fuels the controversy about the role of ANGPTL4 in metabolic homeostasis as discussed earlier. Finally, Lect2 expression was not found to be significantly sensitive to anti-diabetic drugs and phytoestrogens, while Fgf21 expression was strongly stimulated by rosiglitazone and genistein in MPH, in agreement with previous studies in hepatocytes or mesenchymal stem cells [ 125 , 126 ]. However, we could not confirm the induction of Fgf21 expression by metformin as previously suggested by other studies [ 127 , 128 ].…”
Section: Discussionsupporting
confidence: 90%
“…The expression of Zic family member 1 (Zic1), myelin protein zero like 2 (Eva1) or LIM homeobox protein 8 (Lhx8) could not be detected by RT-qPCR in the present study. Therefore, an analysis of the changes between control and treatment groups was not technically possible for these genes in the present study, although previous studies have shown expression of Zic1 in adipogenesis differentiation of C3H10T1/2 cells ( 32 , 33 ). In the future, primary brown adipocyte cells will be used as a model for adipogenesis differentiation in vitro .…”
Section: Discussionmentioning
confidence: 96%
“…Differentiated 3T3-L1 cells were prepared in RIPA lysis buffer (containing protease inhibitors), and total protein concentration was estimated using a Protein BCA Assay Kit (Rockford, IL, USA). Western blot analyses were performed as described in our previous study . An anti-β-actin antibody was used as the loading control.…”
Section: Methodsmentioning
confidence: 99%
“…3T3-L1 cells were transfected with 50 nM AMPKα small interfering RNA (siRNA) (siAMPKα, Santa Cruz Biotechnology) using Lipofectamine 2000 at 80–90% confluency in 6-well plates. The detailed experiments of siAMPKα transfection in 3T3-L1 cells were performed as described elsewhere . The siRNA transfection efficiency was confirmed by qRT-PCR using AMPKα primers (catalog number: sc-29674-PR, Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%